PENGARUH IKLAN TELEVISI PADA EKUITAS MEREK (Fokus Ekonomi, 2009)
The purpose of this research is to identify the impact of television advertising on brand equity. Television advertising dimensions that used are informative/not informative, silliness and pleasure/disturbance. The dimensions of brand equity that used in this study are perceived quality, brand awareness, brand loyalty and brand image. There are twelve hypotheses propose in this study. To answer the hypotheses, researcher employed the survey design and SEM (structural equation modelling) is used to test all hypotheses.The result shows there are positive relationship between informative/non informative with brand awareness, brand image, brand loyalty and perceived quality. There are negative relationship between pleasure/disturbance with brand awareness, brand image and perceived quality but positive relationship with brand loyalty. There are negative relationship between silliness with brand awareness and brand image, but positive relationship with brand loyalty and perceived quality.